PROBLEMS OF TRAINING SPECIALISTS IN THE FIELD OF ENSURING FIRE SAFETY OF PROTECTED OBJECTS - Dr. Serkov B. B; Firsova T. F; Suleimanov A. A; Norpulatov B. N. (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The complex situation of fire science. Two-level system of higher education. Rating assessment and professional competencies.